2015
DOI: 10.1021/acs.nanolett.5b03019
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Printing of Highly Aligned Silver Nanowire Transparent Electrodes for High-Performance Optoelectronic Devices

Abstract: Percolation networks of silver nanowires (AgNWs) are commonly used as transparent conductive electrodes (TCEs) for a variety of optoelectronic applications, but there have been no attempts to precisely control the percolation networks of AgNWs that critically affect the performances of TCEs. Here, we introduce a capillary printing technique to precisely control the NW alignment and the percolation behavior of AgNW networks. Notably, partially aligned AgNW networks exhibit a greatly lower percolation threshold,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
222
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(226 citation statements)
references
References 75 publications
3
222
1
Order By: Relevance
“…3(d), with decreasing GP sizes in ME-TCE films up to 1 mm, higher ϕ TC values can be reached. The optimum ϕ TC value of 85 × 10 −3  Ω −1 with ME-TCEs-GP 1 mm films was much higher than that of 18 × 10 −3 and 36 × 10 −3  Ω −1 for Ag-mesh26 and aligned Ag NWs15, respectively, as well as other TCEs. Additionally, the estimated value showed that further decreases to the optimum GP size below 1 mm would suffer from low transmittance and a significant drop in the ϕ TC value.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…3(d), with decreasing GP sizes in ME-TCE films up to 1 mm, higher ϕ TC values can be reached. The optimum ϕ TC value of 85 × 10 −3  Ω −1 with ME-TCEs-GP 1 mm films was much higher than that of 18 × 10 −3 and 36 × 10 −3  Ω −1 for Ag-mesh26 and aligned Ag NWs15, respectively, as well as other TCEs. Additionally, the estimated value showed that further decreases to the optimum GP size below 1 mm would suffer from low transmittance and a significant drop in the ϕ TC value.…”
Section: Resultsmentioning
confidence: 80%
“…( d ) Φ TC values as a function of transmittance. For comparison, the Φ TC value of Ag mesh45, aligned Ag NW15, Ag nanomesh26, Cu flexible TCEs (FTCEs)46, reduced graphene oxide (RGO)/Au grids4, graphene/Ag grids47, AgCu alloy mesh48, and modified PEDOT:PSS6 are also shown.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42] The performance of the metal NW-based electrode generally increases with the decrease in the diameter of the NW, while the increase in the NW length/diameter aspect ratio will reduce light scattering and decrease the resistance in the film. [43][44][45][46][47][48][49] Therefore, in this study, Ag NWs with an average aspect ratio of 5000 (average diameter of B30 nm and length of 100-200 um, Fig. S1, ESI †) were utilized as the transparent and conductive front-electrodes in the flexible CQD solar cells.…”
Section: Solution-processed Flexible Electrodementioning
confidence: 99%
“…Beyond that, all devices exhibiting a PCE >5% on AgNW electrodes used polymer donors. [25][26][27] In this study, we show aging experiments on organic solar cells with the small molecules α-6T/SubNc/SubPc as cascade. [ 10 ] We compare rigid glass-glass encapsulated devices with ITO bottom electrodes to fully fl exible devices.…”
mentioning
confidence: 99%